Anthropomorphic metaphors in English and Uzbek culinary discourse: a linguocultural analysis - Abdulkhakova, Zulkhumor Fayzullo qizi (The Lingua Spectrum, 2026)
This article examines the linguocultural features of anthropomorphic metaphors in English and Uzbek culinary discourse. The study focuses on the ways food and dishes are represented through human qualities, emotions, and social behaviors in various culinary texts, including recipes, food blogs, restaurant descriptions, and gastronomic advertisements. The research applies comparative linguocultural and discourse analysis methods to identify the semantic and cultural functions of food-related anthropomorphic expressions in both languages. The findings demonstrate that English culinary discourse frequently emphasizes individual sensory experience, emotional comfort, and aesthetic pleasure, while Uzbek culinary texts mainly reflect collectivism, hospitality, social unity, and traditional cultural values. Anthropomorphic metaphors in English often portray food as emotionally expressive and personally engaging, whereas Uzbek culinary expressions present food as a symbol of community, respect, and interpersonal relationships. The study reveals that culinary language functions not only as a means of describing food but also as an important mechanism for transmitting national worldview, cultural identity, and social attitudes through metaphorical representation.